Effect of nanograin-boundary networks generation on corrosion of carburized martensitic stainless steel - Chatdanai Boonruang (2018)
© 2018 The Author(s). Martensitic stainless steel parts used in carbonaceous atmosphere at high temperature are subject to corrosion which results in a large amount of lost energy and high repair and maintenance costs. This work therefore proposes a model for surface development and corrosion mechanism as a solution to reduce corrosion costs. The morphology, phase, and corrosion behavior of steel are investigated using GIXRD, XANES, and EIS. The results show formation of nanograin-boundary networks in the protective layer of martensitic stainless steel. This Cr2O3-Cr7C3nanograin mixture on the FeCr2O4layer causes ion transport which is the main reason for the corrosion reaction during carburizing of the steel. The results reveal the rate determining steps in the corrosion mechanism during carburizing of steel. These steps are the diffusion of uncharged active gases in the stagnant-gas layer over the steel surface followed by the conversion of C into C4-and O into O2-at the gas-oxide interface simultaneously with the migration of Cr3+from the metal-oxide interface to the gas-oxide interface. It is proposed that previous research on Al2O3coatings may be the solution to producing effective coatings that overcome the corrosion challenges discussed in this work.